Pengaruh Faktor Kepuasan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Divisi Finance Accounting Di Pt. Xyz Cabang Head Office - Jessica Novia dan Anas Lutfi (Universitas Tarumanagara, 2019)
The purpose of this study is to examine employee performance of PT. XYZ branch head office. This problem can be seen from the level of turnover and absenteeism has increase from year to year. This study aims to analyze how the influence of job satisfaction factors and work motivation to employee performance and analyze the dominant factor affecting employee performance. This study examine job satisfaction factors (X1) and Work Motivation (X2) towards employee performance (Y).The population in this study were all employees of PT. XYZ branch head office. 80 respondents were taken as sample using Google Form and this data in tought with SPSS program version 23. The analytical method used is multiple regression analysis.Where all independent variance have positive and significant effect on the dependent variable. Adjusted R Square value is equal to 0,89. 89% showed that employee performance variables described by job satisvaction factors and work motivation. The remaining 11% of employee performance is explained by other variables.